Longitudinal Analysis of Neuraminidase and Hemagglutinin Antibodies to Influenza A Viruses after Immunization with Seasonal Inactivated Influenza Vaccines - Mariia V. Sergeeva; Ekaterina A. Romanovskaya-Romanko; Vera Z. Krivitskaya; Polina A. Kudar; Nadezhda N. Petkova; Kira S. Kudria; Dmitry A. Lioznov; Marina A. Stukova; Yulia A. Desheva (Vaccines, 2023)
Neuraminidase (NA)-based immunity could reduce the harmful impact of novel antigenic variants of influenza viruses. The detection of neuraminidase-inhibiting (NI) antibodies in parallel with anti-hemagglutinin (HA) antibodies may enhance research on the immunogenicity and duration of antibody responses to influenza vaccines. To assess anti-NA antibodies after vaccination with seasonal inactivated influenza vaccines, we used the enzyme-linked lectin assay, and anti-HA antibodies were detected in the hemagglutination inhibition assay. The dynamics of the anti-NA antibody response differed depending on the virus subtype: antibodies to A/H3N2 virus neuraminidase increased later than antibodies to A/H1N1pdm09 subtype neuraminidase and persisted longer. In contrast to HA antibodies, the fold increase in antibody titers to NA after vaccination poorly depended on the preexisting level. At the same time, NA antibody levels after vaccination directly correlated with titers before vaccination. A difference was found in response to NA antigen between split and subunit-adjuvanted vaccines and in NA functional activity in the vaccine formulations.